2011
DOI: 10.1111/j.1365-3156.2010.02718.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with patient and health care system delay in diagnosis and treatment for TB in sub‐Saharan African countries with high burdens of TB and HIV

Abstract: Summaryobjective To identify factors causing delayed diagnosis and treatment for tuberculosis in high tuberculosis (TB) ⁄ HIV burden African countries.methods We searched Ovid Medline, CINAHL, PsychInfo, Scopus and Sabinet-South African journals and reference lists, Google, Google Scholar and Google SA for reports in English, ‡1992, of original data from sub-Saharan countries on patient or system delay in TB diagnosis or treatment with populations ‡15 years old. Two reviewers extracted data independently for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 27 publications
1
95
2
7
Order By: Relevance
“…[34][35][36] Although neither travel time nor distance was associated with likelihood of completing TB evaluation at these primary health clinics in Uganda, other studies have found that increased travel time as measured by self-report is associated with delays both in seeking and delivering TB care. 8 In the absence of more detailed individual covariates in our study, we propose several possible hypotheses for testing in future studies. One hypothesis is that patients traveling for a longer time period to access care may be wealthier or more motivated to complete evaluation than those traveling for a shorter period.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[34][35][36] Although neither travel time nor distance was associated with likelihood of completing TB evaluation at these primary health clinics in Uganda, other studies have found that increased travel time as measured by self-report is associated with delays both in seeking and delivering TB care. 8 In the absence of more detailed individual covariates in our study, we propose several possible hypotheses for testing in future studies. One hypothesis is that patients traveling for a longer time period to access care may be wealthier or more motivated to complete evaluation than those traveling for a shorter period.…”
Section: Discussionmentioning
confidence: 95%
“…A number of qualitative studies have highlighted the contribution of geography and extended travel times to failures to complete TB evaluation and initiate treatment, 8 but there is little quantitative information in this area. Geographic information systems (GIS) methods allow investigators to create digital representations of the landscape to enable estimation of the distance that patients travel, a technique that is complementary to information obtained from patient reports and more scalable for data collection on large populations.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de o município investir nas condições de vida, de moradia, escolaridade e de saúde, ainda persistem barreiras geográficas, socioculturais e econômicas que dificultam o acesso dos doentes aos serviços, pois esta população continua nas áreas periféricas, menos favorecidas e vulneráveis ao risco de desenvolver TB (1,3,9,10,15,16).…”
Section: Indicadores De Acesso Ao Diagnósticounclassified
“…A demora na realização do diagnóstico agrava a situação dos doentes, que acabam sendo encaminhados aos níveis secundários e terciários de atenção, já em estado avançado da doença, com sérios comprometimentos da saúde (15,16).…”
Section: Introductionunclassified
“…Some considerable challenges, such as delayed care seeking and poor treatment compliance, 6,7 are resulted from limited community involvement in TB control program. TB programs within community are important to reduce risk infection and decline TB incidence in community.…”
mentioning
confidence: 99%